2020
DOI: 10.3390/w12113241
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hybrid Approach for Water Resources Carrying Capacity Assessment by Integrating Fuzzy Comprehensive Evaluation and Analytical Hierarchy Process Methods with the Cloud Model

Abstract: The water resources carrying capacity (WRCC) shows remarkable fuzziness and randomness, which causes the uncertainty and instability of the WRCC assessment (WRCCA). In order to solve these problems, we proposed a novel hybrid approach for WRCCA, in which the fuzzy comprehensive evaluation (FCE) and analytical hierarchy process (AHP) methods were integrated with the cloud model (CM). Firstly, an evaluation indicator system of WRCC was constructed. Secondly, the AHP and FCE methods were subsequently improved wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In this study, we use fuzzy comprehensive evaluation to evaluate sports smart bracelets. Fuzzy comprehensive evaluation must determine the weight of each indicator, and many scholars have used AHP or EWM for this purpose [ 38 , 39 ]; however, only AHP is used to determine the weight of each evaluation indicator in this study, which makes it easy to obtain decision results with a certain degree of subjectivity. If the EWM is used to determine the weight of each evaluation indicator, it is easy to become divorced from reality.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we use fuzzy comprehensive evaluation to evaluate sports smart bracelets. Fuzzy comprehensive evaluation must determine the weight of each indicator, and many scholars have used AHP or EWM for this purpose [ 38 , 39 ]; however, only AHP is used to determine the weight of each evaluation indicator in this study, which makes it easy to obtain decision results with a certain degree of subjectivity. If the EWM is used to determine the weight of each evaluation indicator, it is easy to become divorced from reality.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of model methods have gradually emerged, such as principal component analysis [5,6] , matter-element model [7,8] , projection pursuit [9,10] , fuzzy evaluation [11][12][13] , multi-objective decision [14][15][16] , water footprint theory [17][18][19] , system dynamics method (SD) [20][21] . With the improvement of the theoretical system, the comprehensive method coupled model evaluation system [22,23] has been further improved, such as DPSIR model [24] , PSR model [25,26] , quality-domain-flow model [27][28] and multi-dimensional cloud model [29][30][31][32] . With the wide application of machine learning technology, neural network algorithm [33][34][35] , genetic algorithm [36,37] and particle swarm optimization algorithm [38,39] have been applied to the quantitative calculation of water resources carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al used the EFAST cloud model [7], and Huang et al developed a water resource security evaluation model based on a combination weight cloud model [8]. Ren et al evaluated the water resource utilization in Datong City, Shanxi Province based on a normal cloud model and improved the accuracy [9]. Their results showed that the cloud model was effective in solving uncertainty problems and has achieved certain practical application effects.…”
Section: Introductionmentioning
confidence: 99%